Impaired learning and memory in mice induced by nano neodymium oxide and possible mechanisms. Issue 8 (2nd May 2021) - Yang, Ning; Yang, Jing; Liu, Yang; Fan, Hongxing; Ji, Le; Wu, Tao; Jia, Dantong; Ye, Qianru; Wu, Gang
Abstract: A growing number of individuals are now exposed to neodymium (Nd) owing to its extensive applications. However, the biological effects of Nd on humans, especially on learning and memory, remain elusive. To investigate whether Nd exposure affects learning and memory, in this study female ICR mice were exposed to nano Nd2 O3 via intranasal instillation at doses of 50, 100, and 150 mg/kg body weight, daily for 45 days. According to Morris water maze data, learning and memory parameters were significantly reduced in the 150 mg/kg nano‐Nd2 O3 group than the sham control. Furthermore, inductively coupled plasma–mass spectroscopy analysis revealed that Nd levels were significantly higher in the hippo campus of the 100 and 150 mg/kg exposed group than the sham control; however, no significant differences were observed in the hippocampal histopathology between these groups. Furthermore, reactive oxygen species were elevated in hippocampal tissues of experimental groups than the sham control, 447.3 in high dose group and 360.0 in control group; however, malondialdehyde levels were significantly increased and superoxide dismutase activities were decreased only in mice exposed to 100 and 150 mg/kg Nd2 O3 . High‐performance liquid chromatography data demonstrated that levels of glutamic acid, glycine, and gamma‐aminobutyric acid were higher in the hippocampus of mice exposed to 150 mg/kg Nd2 O3 than the sham control. Our findings indicated that the neuronal injury was induced by disruption of the oxidation–antioxidation homeostasis and altered amino acid neurotransmitter levels in the hippocampus, which could result in the poor cognitive performance demonstrated by exposed mice.